Interventions to promote the development of motor performance skills in primary school aged children with autism spectrum disorder: A systematic review and meta-analysis of controlled trials - Sortwell, A.; Forte, P.; Ramirez Campillo, R.; Trimble, K.; Steel, K.; O'Brien, K.; Neiva, H. P.; Marinho, D. A.; Ferraz, R. (International Journal of Kinesiology & Sports Science, 2022)
Background: The development of proficiency in motor performance skills (MPS) builds the foundation for the complex movement skills required to participate in a range of sports and physical activities throughout the lifespan. Objective: To assess the efficacy of different intervention approaches on developing MPS proficiency in children with autism spectrum disorder (ASD) and examine the intervention factors that influence change. Method: Searches were completed in three databases (PubMed/MEDLINE, Scopus, Web of Science) up to March 2022. Only randomised controlled trials (RCTs) or controlled trials (CTs), that evaluated the effectiveness of interventions on overall MPS proficiency or specific MPS such as balance, running speed and agility, bilateral coordination, jumping, ball skills and push-ups in children (4-13 years old) were included. The DerSimonian and Laird random-effects model was used to compute the meta-analyses. The effect sizes were reported as Hedges` g. Using a random-effects model, potential sources of heterogeneity were identified, including subgroup analyses (type of intervention), and single training factor analysis (total number of weeks, session frequency, total intervention time, total number of training sessions). In addition, a multivariate meta-regression calculation was performed for balance. The GRADE framework was applied to assess certainty of evidence. Results: Seventeen interventions (13 RCTs and 4 CTs) revealed significant differences among groups favouring the intervention group with moderate to very large effects. Significant (p < 0.05) small-to-large effects of interventions were evident on overall motor performance skills (ES = 2.43), ball skills (ES = 2.95), jumping (ES = 1.89), bilateral coordination (ES = 2.21), push-ups (ES = 1.92), balance (ES = 1.56), running speed and agility (ES = 1.31). Multivariate meta-regression for balance revealed that total sessions, total intervention time and session frequency predicted (p = 0.009, p<0.001, p = 0.036, respectively) the effects of interventions on change in balance performance. Conclusion: Structured interventions that explicitly teach traditional FMS or promote the development and learning of movement skills specifically associated with a type of physical activity or sport, effectively improve MPS in children with ASD. Education settings should implement `planned` movement experiences or interventions as a strategy to promote MPS proficiency in children with ASD.